THE EFFECT OF DISCOUNT VOUCHERS ON THE IMPULSIVE BEHAVIOR AND FINANCIAL MANAGEMENT OF REGIONAL STUDENTS - Arie Citra Mardiana; Daris Hikmah (Count : Journal of Accounting, Business and Management, 2024)
The purpose of this research is to explore that there are still many regional students who have an impulsive attitude towards buying food online just because they are attracted by discount vouchers provided by e-commerce applications and result in financial management being less than optimal. The method applied by the researcher is a quantitative approach with questionnaires distributed to regional students and using food e-commerce applications. The number of respondents in this study was 101 respondents. To analyze the data, the researcher applied validity tests, reliability tests, normality tests, and hypothesis tests by applying the Multivariate Analysis Of Variance (MANOVA) technique. Based on the research that has been conducted, researchers revealed that discount vouchers affect impulsive behavior and financial management of students who travel. This disclosure can be seen in the final results of the Multivariate Test with a value of Sig. < 0.05, as well as in the Univariate Significance Test for impulsive behavior and financial management which shows a value of Sig. < 0.05.